Side-Lit Window Design for Optimum Daylighting in Library Reading Areas - Dahlan, Nur Dalilah (2005)
Conventional tropical building designs are experiencing new paradigm in its environmental response to improve lighting ambiance and users' comfort by exploiting daylighting. This research focused on accessing existing daylight factors, illuminance levels, users' preference and their perception towards daylight library reading areas. The performance of daylighting applied in library design in tropical country like Malaysia is evaluated based on their Side-Lit Window Design (SLWD). Daylighting evaluation is done through three methodologies, namely, via Field Measurement; Computer Simulation and User Survey. Reading areas in three libraries have been identified as case studies. The libraries selected are Perpustakaan Sultan Abdul Samad (L.l), Universiti Putra Malaysia (UPM), Perpustakaan Tun Abdul Razak 1 (L.2), Universiti Teknologi MARA (UiTM) and the Main Library of International Islamic University of Malaysia (L.3). By applying the Window to Wall Ratio (WWR) and Window to Floor Ratio (WFR), each window design from the case study is classified into three Typical Daylighted Bays (TDB), which are; low WFR (0.2) with moderate headroom height (3m high); high WFR (0.4) with moderate headroom height and high WFR with high headroom height (4 m).Illumination level readings are collected at three separate periods of a day, namely, in the morning, afternoon and evening. Measurements are indicated using portable Konica-Minolta Illuminance Meter T10 at 7 'P' test points lm apart from each other starting from the windows of each TDB. Parametric analyses using RadianceIES predicted potential window and interior criteria applicable in designing of future daylighting designs in large public indoor areas. The simulations are generated under '10K CIE Overcast Sky' file to predict daylighting performance during worst case scenario affects in a tropical country. Furthermore, the survey carried out measured users' comfort and awareness according to impacts shown in relation to three different SLWD. The responses are recorded via questionnaires issued to them at each of the selected TDB. The surveys are performed during diurnal operation hours of the particular libraries. Findings revealed that window design at the reading area in L.3 with WWR of 0.76, WFR of 0.43 and headroom height of 4m allowed sufficient daylight transmittance. However, users at this particular TDB complaint of too much daylighting within 7m distance from the windows. Further parametric analyses revealed that at WWR of 0.5 achieved a close approximate of DF with WWR of 0.76. Therefore SLWD with WWR of 0.5 can promote effective daylighting up to 3% of DF within 4m distance from the windows in deep interior building such as libraries.